Strategi Marketing Public Relations Nasi Kebuli Al-Khalid dalam Meningkatkan Brand Image - Ryvaldo Fernando; Riza Hernawati (UNISBA Press, 2024)
Abstract. Due to high competition at this time, entrepreneurs are indirectly required to make optimal and maximum efforts to improve the quality, taste and products produced. These efforts are made to ensure that the business meets expectations, fulfills its goals, and presents a positive image to the public. Marketing Public Relations is an action to establish communication between companies and consumers. Marketing public relations has 3 strategies, namely pull strategy, push strategy, pass strategy. The purpose of this research is to determine the strategies used by the marketing and public relations department of Nasi Kebuli Al-Khalid to improve its brand image. Descriptive methodology with interview data was used in this research. Based on the research results, Nasi Kebuli Al-Khalid's pull strategy is carried out through publications as an effort to convey information to consumers and is carried out online through websites, social media and food ordering service applications. Apart from that, publication is carried out offline using banners or billboards when opening a new restaurant branch. The push strategy is carried out by carrying out promotions by providing discounts on food ordering service applications and offline by considering the image of